Herbal Medicine (HM) among pharmacy professionals working in drug retail outlets in Asmara, Eritrea: knowledge, attitude and prevalence of use - Alemseghed Goitom; Feruz Yemane; Mussie Tsegay; Amanuel Kifleyesus; Senai Mihreteab Siele; Eyasu H. Tesfamariam; Nuru Abdu (BMC, 2022)
Abstract Background Globally, the usage of herbal medicines (HMs) is increasingly growing in treating and preventing various ailments. Although, HMs play a vital role in healthcare, concerns have been raised over their safety. Since pharmacy professionals are at the right position to provide patients with evidence-based information on herbals, they should be knowledgeable enough on the subject matter. Thus, the aim of the study was to assess the knowledge, attitude and prevalence of HMs use and its associated factors among pharmacy professionals. Method An analytical cross-sectional study was conducted among pharmacy professionals working in drug retail outlets in Asmara (the capital city of Eritrea). A census design was employed and data were collected through face-to-face interview. Data were entered and analyzed using Census and Survey Processing System (version-7.2) and IBM Statistical Package for Social Sciences (version 26), respectively. Descriptive and analytical statistics including Mann-Whitney U test/Kruskal-Wallis test and logistic regression were employed. P-values less than 0.05 were considered as significant. Results A total of 50 pharmacy professionals (90.9% response rate) were enrolled in the study. Majority of them (62%) were males and two-thirds had a bachelor's degree. The overall median (Interquartile range, IQR) knowledge score was found to be 24 (12.16) out of 100 with a minimum score of 8 and maximum score of 53. Generally, the median (IQR) attitude score was 70.4 (4.2) out of 100. Majority (78%) of them had used HM for self-treatment. Only religion was found to be a significant determinant of knowledge on indication of HMs (p = 0.015), while attitude score was independent of the potential determining factors. Moreover, prevalence of use was significantly associated with pharmacy ownership (Adjusted Odds Ratio (AOR) =14.44, 95%Confidence Interval (CI): 1.67, 124.52) as well as with the percentage attitude score (AOR = 0.632, 95%CI: 0.41, 0.96) at multivariable level. Conclusion Generally, the overall knowledge score of pharmacy professionals was low. However, they possessed positive attitude towards herbal medicines. Besides, there was prevalent usage of herbal medicine for self-treatment. This outcome triggers the need for educational courses and workshops centered on herbal medicine.